The co-operative movement and communities in Britain, 1914-1960 : minding their own business - Robertson, Nicole (Studies in labour history (Ashgate (Firm)), 2010)
This book provides the first major national study of the growth of co-operation and its impact on British society during this crucial period of war and peace.